2016
DOI: 10.5267/j.ccl.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Schiff bases of 4-(methylthio)benzaldehydes: Synthesis,characterization, antibacterial, antioxidant and cytotoxicity Studies

Abstract: A series of new Schiff bases of 4-(methylthio)benzaldehyde derivatives 3(a-i) were synthesized by the reaction of 4-(methylthio)benzaldehyde with various amines 2(a-i). Newly synthesized compounds were characterized by elemental analyses, UV-visible, FT-IR, Mass and 1 H NMR spectral studies. All compounds were evaluated for their in vitro antibacterial activity against clinically isolated strains i.e., E. Coli, P. Fluorescence, M. Luteus and B. Subtilis. These compounds were screened for their antioxidant acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In relation to our results of free iron levels, a significant reduction was observed in connective tissue homogenates of N. cinerea after treatment with NW05 (10 mM) e NJ20 (10 mM) ( Figure 6 ). It has been reported that certain thiazoles have excellent free Fe 2+ chelating capacity and moderate toxicity, which could justify the results found here [ 60 ].…”
Section: Discussionsupporting
confidence: 86%
“…In relation to our results of free iron levels, a significant reduction was observed in connective tissue homogenates of N. cinerea after treatment with NW05 (10 mM) e NJ20 (10 mM) ( Figure 6 ). It has been reported that certain thiazoles have excellent free Fe 2+ chelating capacity and moderate toxicity, which could justify the results found here [ 60 ].…”
Section: Discussionsupporting
confidence: 86%
“…Finally, in addition to lipid peroxidation, it was observed here depletion in free Fe 2+ ion contents in N. cinerea head homogenates for all concentrations of guarana powder decoction (Figure 11), which might as well infer the potential antioxidant capacity of P. cupana. Indeed, substances capable of chelating free iron are categorized as antioxidant compounds, broadly used in toxic-pharmacological studies (Karthik et al, 2016;Schneider et al, 2019). Similar to our results, Pereira et al (2022) reported a significant reduction in Fe 2+ ion content in connective tissue homogenates of N. cinerea after treatment with Thiazolidine compounds NW05 (10 mM) e NJ20 (10 mM).…”
Section: Discussionsupporting
confidence: 88%
“…Interesting antioxidant activities have been exhibited by the reported phenylhydrazones compared to the standard drug, vitamin C. A progressive increase in the percentage antioxidant activity with increasing concentration of test compounds as depicted in Table 2 and Figure 7 was recorded [17]. Based on the calculated IC 50 values, Prmpp-Ph has shown a stronger antioxidant property overall, with an IC 50 value of 175.66 g/ml followed by Empp-Ph with an IC 50 of 193.90 g/ml.…”
Section: Antioxidant Studies Against Dpphmentioning
confidence: 95%
“…Tridentate 3-formyl chromone Schiff bases showed good antioxidant activities against DPPH at different concentrations with as low as 1.27 g/ml IC 50 value compared to standard drug BHT (IC 50 value of 0.67 g/ml) [16]. More recently, Karthik and fellow researchers synthesized a series of Schiff bases with 4-(methylthio)benzaldehydes that have shown to highly scavenge free radicals [17]. Acylpyrazolone Schiff bases synthesized from the condensation reaction of some acylpyrazolone derivatives with sulfanilamide that showed antioxidant properties have been reported by our group [18].…”
Section: Introductionmentioning
confidence: 99%